Bone metabolic indices: Promising predictors for assessing acromegaly. (May 2022) - Zhu, Wei; Wei, Zhanqi; Guo, Xiaopeng; Wang, Zihao; Deng, Kan; Lian, Wei; Yang, Bo; Xing, Bing
Highlights: β-CTX and TP1NP decrease with the remission of acromegaly. Bone destruction and formation is correlated with β-CTX and TP1NP levels. β-CTX is an independent risk factor to predict the level of SAGIT score. Abstract: Acromegaly is a chronic progressive endocrine disease that is often accompanied by joint and bone symptoms. The correlation between bone metabolism and acromegaly is still unclear. In this study, 31 patients with acromegaly at Peking Union Medical College Hospital were included. Bone metabolism indices, such as β-CTX, TP1NP, T-25OHD, 1, 25(OH)2D3, and SAGIT score, which represent the severity of acromegaly, were examined before operation, and the patients were followed up for at least 3 months after operation. The results showed that β-CTX and TP1NP were significantly lower than those before surgery in the remission group (p < 0.001). In the nonremission group, CTX (p = 0.226) and TP1NP (p = 0.326) did not show significant differences from those before operation. In Pearson correlation analysis, β-CTX was significantly correlated with SAGIT score (r = 0.356, p = 0.049). By multivariate linear regression analysis, it was found that β-CTX was an independent risk factor of SAGIT score (p = 0.001). In conclusion, indicators of bone metabolism are closely related to changes in acromegaly, and the β-CTX value can be used as an effective predictor for assessing acromegaly.